Urban Characteristics Influencing Health of Older People: What Matters - Moses Wong, Jean Woo, Ruby Yu,; Leung, Jason; Lau, Kevin; Ho, H.C.; Teresa Tsien, Alma Au, H.M. Yip, Jackie Kwok, Daniel W.L. Lai, (International Journal of Innovative Research in Medical Science, 2017)
Background: Most studies examining the impact of the physical environment on health outcomes have been carried out in urban cities in the United States, Europe, or Australia, where population density and building architecture may be quite distinct from densely populated Asian cities. This study examines characteristics of urban environment in two highly contrasting regions of Hong Kong, exploring the effects of population and building density, accessible micro environment, air pollution, and social deprivation on health outcomes, using an ecological design. Methods: A convenience sample of residents aged 60 years and older was carried out between July and December 2015. Data for four contrasting districts were examined based on differences in population density and urban development. Self-rated health and loneliness were used as health outcome indicators. Socio-demographic and geographic characteristics, air quality, health service provision, and social vulnerability of districts were documented. Spearman rank correlation was used to analyze the association between the different factors and health outcomes. Results: Univariate correlation shows that self-rated health was poorer among the older age group, women, and in areas with greater population density and building height, poorer air quality, and higher prevalence of social vulnerability. Self-rated health was positively associated with a higher sky view factor, more open spaces and vegetation, more hospitals and hospital beds, and ambient ozone. Loneliness was inversely associated with education levels although the association was weak. Conclusion: In densely populated cities such as Hong Kong, design of health-promoting urban environments for ageing populations should consider building density, height, and green spaces, as well as provision of health services, in order to contribute to health equity.